Stress hormonal analysis in elite soccer players during a season - Michailidis, Y. (Journal of Sport and Health Science, 2014)
Purpose: The purpose of this study was to evaluate the changes in some hormonal parameters (cortisol, testosterone, ratio of testosterone/cortisol (T/C)) in professional soccer players during a season. Methods: Fifteen professional players from a soccer club of the first division of the Greek soccer league participated. All sport medical examinations were conducted four times: before the re-building period, post re-building period, mid-season, and after finishing the competition phase. Results: For testosterone, significant differences were observed between the end season and post re-building period (11.6%; p < 0.05) and mid-season (12.1%; p < 0.05). The cortisol concentration increased at mid-season by approximately 23%, and this change differed significantly from all other measurements for this hormone. The T/C ratio increased at the post re-building period and decreased at the middle of the season. Conclusion: These hormones and their ratios could be used as stress and recovery state indicators. Coaches can use these parameters in combination with other indicators to optimize workloads, and to avoid overreaching and overtraining.